1986
DOI: 10.1111/j.1399-3011.1986.tb01059.x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and conformational study of two L‐prolyl‐L‐leucyl‐glycinamide analogues with a reduced peptide bond

Abstract: The peptide bond between Pro‐Leu or Leu‐Gly in Pro‐Leu‐Gly‐NH2 was replaced by a CH2‐NH function. The 1H and 13C n.m.r. studies demonstrated that HCl·Pro‐Leu (CH2‐NH)Gly‐NH2 10 adopted a conformation in DMSO that is similar to the previously postulated β‐turn for the natural hormone. This was not the case for the other analogue. In vivo tests on 10 revealed an activity approximately equal to the natural compound and an increased toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Clinical assays demonstrated that MIF-1, alone, has the potential to alleviate the motor symptoms of PD, , to potentiate the effect of levodopa when used in a cotherapy regimen, and to reduce the levodopa-induced dyskinesia . Despite its great potential, pharmacokinetic issues associated with this neuropeptide (e.g., low gastrointestinal absorption and lability toward CNS proteases) hinder the progression of clinical assays and its use in PD. Over the years, several strategies have been employed to improve the stability and activity of MIF-1, including the development of peptidomimetics, and chemical conjugation with a sinapic acid at the N -terminal and biogenic amines as spacers at the C -terminal position …”
mentioning
confidence: 99%
“…Clinical assays demonstrated that MIF-1, alone, has the potential to alleviate the motor symptoms of PD, , to potentiate the effect of levodopa when used in a cotherapy regimen, and to reduce the levodopa-induced dyskinesia . Despite its great potential, pharmacokinetic issues associated with this neuropeptide (e.g., low gastrointestinal absorption and lability toward CNS proteases) hinder the progression of clinical assays and its use in PD. Over the years, several strategies have been employed to improve the stability and activity of MIF-1, including the development of peptidomimetics, and chemical conjugation with a sinapic acid at the N -terminal and biogenic amines as spacers at the C -terminal position …”
mentioning
confidence: 99%